PP.21.33: THE MICROBIAL METABOLITE, BUTYRATE ATTENUATES PULMONARY HYPERTENSION. (June 2015) - Shenoy, V.; Yang, T.; Rathinasabapathy, A.; Horowitz, A.; Katovich, M.; Raizada, M.
Abstract : Objective: The gut microbiota harbors a complex community of microbial cells, which influence human physiology, metabolism, and immune function. Disruption of the gut microbiota has been linked to gastrointestinal conditions, inflammatory bowel disease, obesity, and neurodegenerative diseases. However, the role of the gut microbiota in lung diseases such as pulmonary hypertension (PH) has not been elucidated. Our goal in this study was to evaluate the hypothesis that alterations in the gut microbial composition is linked to PH and demonstrate that administration of butyrate, a short chain fatty acid secreted by the commensal bacteria can exert protective effects against PH. Design and method: PH was induced in male Sprague Dawley rats by single subcutaneous injection of monocrotaline (MCT, 50 mg/Kg). A subset of MCT animals was divided into two protocols: prevention and reversal. For the prevention study, treatment with butyrate (500 mg/kg, ip) was initiated immediately after MCT injection, while for the reversal protocol, butyrate treatment was commenced after 2-weeks of MCT challenge. At the end of 4-weeks of MCT administration, echocardiographic and hemodynamic measurements were determined and fecal samples were collected for microbiome analyses. Results: MCT rats exhibited marked increase in right ventricular systolic pressure (RVSP; Control: 30 ± 2mmHg; MCT: 87 ± 3mmHg), along with the development of right ventricular hypertrophy (RVH; Control: 0.26 ± 0.005; MCT: 0.61 ± 0.01). Furthermore, we observed significant changes in the composition of the gut microbiota (Actinobacteria, Bacteroidetes and Proteobacteria). This was associated with decreased levels of butyrate in MCT animals as compared with controls, suggesting a microbial dysbiosis. Chronic treatment of MCT rats with butyrate provided protection in both the prevention and reversal protocols. In the prevention study, butyrate showed 36% decrease in RVSP (MCT + butyrate: 55 ± 8mmHg) and 29% reduction in RVH (MCT + butyrate: 0.43 ± 0.04), while in the reversal study a 25% decrease in RVSP (MCT + butyrate: 65 ± 8mmHg) and 22% reduction in RVH (MCT + butyrate: 0.47 ± 0.04) was observed. Collectively, our results demonstrate that butyrate treatment significantly improves right heart function. Conclusions: Our findings indicate that PH is associated with microbial dysbiosis and that treatment with butyrate, a beneficial microbial metabolite confers protection against MCT-induced PH.